Novel Insight on Organoleptic Water Quality and Menstrual Hygiene at Secondary Schools: A Cross-Sectional Study in Batanghari Regency, Sumatera, Indonesia - Julia Putri Hayuni; Zakianis Zakianis; Laila Fitria; Ema Hermawati; Sifa Fauzia; M. Romli; Sari Yuli Andarini (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Menstrual hygiene management (MHM) practices among female students in Indonesia remain low (35.9%), increasing the risk of urinary tract and reproductive infections. While access to water is commonly studied in relation to MHM, few studies in Southeast Asia have examined how the sensory quality of water (organoleptic properties) influences hygiene behaviors. This study addresses that gap by analyzing the relationship between organoleptic water quality and MHM in schools among female students in Batanghari Regency. Methods: A cross-sectional study was conducted with 342 female students from 93 secondary schools in Batanghari Regency. Data were analyzed using chi-square test and binary logistic regression. Results: Although 60.5% of female students attended schools with good organoleptic water quality, only 36.5% practiced good MHM at school. MHM at schools were associated with organoleptic water quality; water availability; soap availability; availability of safe toilets; availability of closed waste bins, parental support; teacher support; friend support; maternal education, paternal education, and knowledge. Furthermore, a significant relationship was found between organoleptic water quality interacting with availability of safe toilets for MHM after controlling for confounding variables (AOR: 3.987-26.710). Conclusion: Good MHM practices among female students are low. Schools and authorities should improve WASH facilities, protect water sources, and ensure toilets safety. Communication channels should allow students to report issues promptly. Teacher training on menstrual health should be prioritized, and menstrual health education should be integrated into the curriculum to improve knowledge, reduce stigma, and empower female students.